2010
DOI: 10.4314/bcse.v24i1.52980
|View full text |Cite
|
Sign up to set email alerts
|

<b>Physicochemical attributes of oils from seeds of different plants in Nigeria</b>

Abstract: The physicochemical qualities of oils from seeds of seven plants grown in Nigeria were evaluated. Physical characterization of the oils includes viscosity, state at room temperature, colour, specific gravity and refractive index. The results showed that they have different colors and are consistently liquid at room temperature. The viscosity of the oils varied; P. macrophylla had the highest viscosity of 19.55 cST while D. edulis had the least value of 11.00 cST. The specific gravity of all the oils ranged bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
(22 reference statements)
3
7
1
Order By: Relevance
“…The values of the present study are higher than those documented for Lannea kerstingii (Ouilly et al., ) and Allanblackia floribunda (Wilfred, Adubofuor, & Oldham, ). However, our documented values are within the range reported by Taha, Nour, and Elkhalifa () but lower than those values reported in other studies such as Ajayi () and El‐Siddig et al. ().…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The values of the present study are higher than those documented for Lannea kerstingii (Ouilly et al., ) and Allanblackia floribunda (Wilfred, Adubofuor, & Oldham, ). However, our documented values are within the range reported by Taha, Nour, and Elkhalifa () but lower than those values reported in other studies such as Ajayi () and El‐Siddig et al. ().…”
Section: Discussionsupporting
confidence: 73%
“…Peroxide value indicates the degree of oxidation of the oil—low peroxide value indicates low oxidation (Ekop et al., ). The present study values are above the values reported for most common plants (Ajayi, ; Ekop et al., ; Muhammad et al., ; Ouilly et al., ; Wilfred et al., ). This value is above the range of peroxide values (<10 mEq/kg) generally reported for fresh fats and oils (Kirk & Sawyer, ).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The iodine value sorts the oil in the range of cotton seed oil or corn oil ( Gossypium hirsutum and Zea mays , resp.) [27, 28] while the saponification value is somewhat higher, like Tamanu oil ( Calophyllum inophyllum ) [29]. Saponification values exceeding 200 are quite rare cases, which may be important for specific industrial applications.…”
Section: Resultsmentioning
confidence: 99%